2023
DOI: 10.3390/su15107847
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on the Performance of SMEs in Emerging Markets in Iran, Iraq and Jordan

Abstract: This research aims to investigate the effect of COVID-19 on the performance of small and medium enterprises (SMEs) in emerging markets in Iran, Iraq and Jordan. In order to collect the required data, a standard questionnaire provided in the literature was used. The research period is the second quarter of 2022, and its population includes managers, accountants and auditors engaged in listed and non-listed companies. The research findings indicate that the outbreak of COVID-19 has affected SMEs’ performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Their results showed that those firms suffered most from the fragility of their management system and the lack of financing. This result is consistent for other countries, for example, Homayoun et al (2023) examined the impact of the COVID-19 pandemic on small and medium enterprises (SMEs) in emerging markets such as Iran, Iraq, and Jordan. The researchers used a standard questionnaire to collect data from managers, accountants, and auditors in both listed and non-listed companies during the second quarter of 2022.…”
Section: The Impact Of the Covid-19 Health Crisis On Female-led Firms...supporting
confidence: 75%
See 1 more Smart Citation
“…Their results showed that those firms suffered most from the fragility of their management system and the lack of financing. This result is consistent for other countries, for example, Homayoun et al (2023) examined the impact of the COVID-19 pandemic on small and medium enterprises (SMEs) in emerging markets such as Iran, Iraq, and Jordan. The researchers used a standard questionnaire to collect data from managers, accountants, and auditors in both listed and non-listed companies during the second quarter of 2022.…”
Section: The Impact Of the Covid-19 Health Crisis On Female-led Firms...supporting
confidence: 75%
“…Small and medium-sized enterprises (SMEs) face heightened vulnerability compared with other types of firms, particularly during times of crisis due to their limited time and resources (Markovic et al, 2021). These constraints significantly impact the operations and performance of these firms (Homayoun et al, 2023;Veselinova & Samonikov, 2021). In the analysis of the evolving impact of the health crisis on Moroccan female-led firms, by size in nine regions of Morocco, we find evidence of gender disparities, both in terms of firm closures and adaptability to the crisis.…”
Section: The Impact Of the Covid-19 Health Crisis On Female-led Firms...mentioning
confidence: 99%
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…Zdolsek and Taskar Beloglavec noted that "awareness of sustainability issues has improved, leading to improved sustainability reporting", as COVID-19 "had no effect on the dynamics of change in the ecosystem of non-financial reporting announcements" [10]. In Iran, Iraq, and Jordan, the sustainable business models of SMEs "shifted slightly from technological to social, customer and organisational changes", motivating SMEs to rethink their core competencies and redefine their sustainability, while the pressure of pandemic restrictions improved and increased the change and innovation components of SMEs [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%